The effect of slow deep breathing on lowering blood pressure in the elderly with hypertension: A systematic review - Nuridah Nuridah; Etty Rekawati; Yossie Susanti Eka Putri; Ikhwanudin Ikhwanudin (Malahayati International Journal of Nursing and Health Science, 2025)
Background:  Increasing age causes an increase in blood pressure in the elderly which results in the emergence of various infectious to degenrative diseases, one of which is hypertension. Hypertension is an increase in systolic blood pressure exceeding 140 mmhg and diastolic 90 mmhg. One of the efforts in handling hypertension is with non-pharmacological therapies such as slow deep breathing exercises that play a role in stimulating the work of parasympathetic nerves and inhibiting sympathetic nerves to lower blood pressure in hypertensive elderly. Purpose: To determine the effect of slow deep breathing on lowering blood pressure in elderly with hypertension. Method: Systematic review approach by analyzing selected literature from various sources. Article searches were conducted through online databases, namely ProQuest, ScienceDirect and Goggle Scholar. The results of the article selection obtained 8 articles  that met the criteria and were analyzed and critiqued using the JBI instrument ... Quality assessment is based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) checklist. Results: Slow deep breathing is a nonpharmacological therapy that is proven to be able to reduce blood pressure in elderly people with hypertension. Conclusion: The role of slow deep breathing (SDB) is proven to be effective in helping reduce blood pressure in the elderly with hypertension.